Expression of glutathione, glutathione peroxidase and glutathione S-transferase pi in canine mammary tumors - Leonel, Camila [UNESP]; Gelaleti, Gabriela B. [UNESP]; Jardim, Bruna V. [UNESP]; Moschetta, Marina G.; Regiani, Vitor R.; Oliveira, Juliana G.; Zuccari, Debora A. P. C. (Biomed Central Ltd., 2014)
Background: Glutathione (GSH) is one of the most important agents of the antioxidant defense system of the cell because, in conjunction with the enzymes glutathione peroxidase (GSH-Px) and glutathione S transferase pi (GSTpi), it plays a central role in the detoxification and biotransformation of chemotherapeutic drugs. This study evaluated the expression of GSH and the GSH-Px and GSTpi enzymes by immunohistochemistry in 30 canine mammary tumors, relating the clinicopathological parameters, clinical outcome and survival of the bitches. In an in vitro study, the expression of the genes glutamate cysteine ligase (GCLC) and glutathione synthetase (GSS) that synthesize GSH and GSH-Px gene were verified by qPCR and subjected to treatment with doxorubicin, to check the resistance of cancer cells to chemotherapy.Results: The immunohistochemical expression of GSH, GSH-Px and GSTpi was compared with the clinical and pathological characteristics and the clinical outcome in the bitches, including metastasis and death. The results showed that high immunoexpression of GSH was correlated to the absence of tumor ulceration and was present in dogs without metastasis (P < 0.05). There was significant correlation of survival with the increase of GSH (P < 0.05). The expression of the GSH-Px and GSTpi enzymes showed no statistically significant correlation with the analyzed variables (p > 0.05). The analysis of the relative expression of genes responsible for the synthesis of GSH (GCLC and GSS) and GSH-Px by quantitative PCR was done with cultured cells of 10 tumor fragments from dogs with mammary tumors.The culture cells showed a decrease in GCLC and GSS expression when compared with no treated cells (P < 0.05). High GSH immunoexpression was associated with better clinical outcomes.Conclusion: Therefore, high expression of the GSH seems to play an important role in the clinical outcome of patients with mammary tumors and suggest its use as prognostic marker. The in vitro doxorubicin treatment significantly reduces the expression of GCLC and GSS genes so we can consider them to be candidates for predictive markers of therapeutic response in mammary cancer.
Keywords: Mammary neoplasia; Glutathione; Immunohistochemistry; Real-time PCR; Oxidative stress